Substrate specificity of the cypemycin decarboxylase CypD - Wei Ding; Tianlu Mo; Dhanaraju Mandalapu; Qi Zhang (Synthetic and Systems Biotechnology, 2018)
The linaridin antibiotic cypemycin is a ribosomal synthesized and post-translationally modified peptide (RiPP) that possesses potent activity against mouse leukemia cells. This peptide natural product contains an S-[(Z)-2-aminovinyl]-d-cysteine (AviCys) moiety in the C-terminus. Formation of AviCys moiety requires an oxidative decarboxylation of the C-terminal Cys of the precursor peptide CypA, and this process is catalyzed by a flavin-containing protein CypD. In this work, we tested CypD substrate specificity with a series of synthetic oligopeptides. We show that most of the N-terminal sequence of CypA is not required for CypD activity, and the C-terminal three residues serve as the minimal structural element for enzyme recognition. We also show that CypD tolerates various substrates with modified C-termini, allowing for the generation of four novel cypemycin variants with modified AviCys moiety by site direct mutagenesis of the precursor peptide CypA. Our study demonstrates the relaxed substrate specificity of CypD and lays a foundation for future bioengineering of AviCys-containing natural products.